Identifikasi Bakteri Staphylococcus aureus Pada Tombol Elevator / Lift di Gedung Fakultas Kedokteran dan Ilmu Kesehatan Universitas Atma Jaya Jakarta - Rachmad, Basuki; Apriani, Apriani; Afiyah, Ida (JURNAL KESEHATAN TERAPAN, 2022)
Staphylococcus aureus is one of the most common pathogens that cause infection in humans. S. aureus is a Gram-positive bacterium in the form of cocci, immobile, non-sporing, facultative anaerobic and can grow in air containing only hydrogen. This study aims to isolate and identify S. aureus bacteria on the elevator button at the FKIK Atma Jaya building, Jakarta. This study used a descriptive method, which was carried out on 28 samples of elevator buttons from 3 elevators in 3 FKIK Atma Jaya Jakarta buildings by swab the surface of the elevator buttons 2 times in the morning and evening, tested macroscopically, microscopically and biochemically. In BA medium, bacterial colonies were round, gray in color, and there was hemolysis, followed by MSA, Gram, catalase, coagulase and mannitol tests which showed positive results. Of the 28 samples, positive results were obtained for S.aureus only on the 5th floor of the Damianus building in the afternoon. The discovery of S. aureus bacteria was suspected because the mobilization in the Damianus building was quite high compared to other buildings. This research can be used as a reference for future researchers, that further research is needed to identify other pathogenic bacteria on elevator buttons. Keywords: Staphylococcus aureus, pathogens bacteria, elevator buttons